PENINGKATAN POTENSI EKONOMI MASYARAKAT DESA MELALUI PELATIHAN PEMBUATAN PIE NANAS DI DESA LENDANG NANGKA UTARA - Anang Wahyudi Adnan; Nida Shaffitrri Hafidz; Linda Sari; Nur Melinda; Windy Pratiwi Candra Santoso; Muhammad Ilham Fikri; Baiq Nur Alya; Muhammad Agus Ripa’i; Mira Fitri Cahyani; Sahrul Fadli; Giri Wahyu Wiriasto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Mataram, 2023)
Lendang Nangka Utara Village is located in the Masbagik Subdistrict, covering an area of 900 hectares. This village is renowned for its abundant natural resources, particularly pineapples. However, an issue observed in this village is the underutilization of these available natural resources. Pineapples, which are an iconic produce of Lendang Nangka Utara Village, should be processed into various products such as pineapple chips, pineapple jam, pineapple candy, pineapple pies, and more. Nonetheless, a majority of the residents in Lendang Nangka Utara Village who have pineapple farms merely sell the fruit without engaging in the production process to create value-added products. The Community Empowerment Real Work Lecture (Kuliah Kerja Nyata) aims to harness the existing resources in Lendang Nangka Utara Village to develop creative and innovative processed products. The chosen sample product for utilizing the available pineapple resources is pineapple pie. The program involves both socialization and training sessions for pineapple pie making. The socialization efforts aim to instill an entrepreneurial spirit within the community of Lendang Nangka Utara Village. Additionally, the pineapple pie training is designed to provide insights to the local community on how pineapples can be transformed into a product with higher market value compared to selling them solely as fresh fruits.